2012
DOI: 10.1016/j.enbuild.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance impacts of center-of-glass deflections in installed insulating glazing units

Abstract: This study examines the thermal performance impact of center-of-glass (COG) deflections in double-and triple-pane insulating glass units (IGUs) installed at several locations throughout the US. Deflection was measured during summer and winter temperatures; the results show that outdoor temperature variations can be represented a linear change in COG gap width in doubleand triple-pane IGUs within the temperature ranges measured. However, the summer-winter temperature-induced deflection is similar in magnitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Due to need for separating different parts of the window for simulation of one square meter of triple-glazing glass and measuring the factors related to glass simulation, we have used WINDOWS 6 for its efficiency and capability for our purpose. Reliability of the measures and the results has been proved by various tests and measurements (Smith et al, 2012;Hart et al, 2012). Finally, after gaining the data, findings were changed into charts by Grapher 9 software so that their analysis would be easy.…”
Section: Methodsmentioning
confidence: 99%
“…Due to need for separating different parts of the window for simulation of one square meter of triple-glazing glass and measuring the factors related to glass simulation, we have used WINDOWS 6 for its efficiency and capability for our purpose. Reliability of the measures and the results has been proved by various tests and measurements (Smith et al, 2012;Hart et al, 2012). Finally, after gaining the data, findings were changed into charts by Grapher 9 software so that their analysis would be easy.…”
Section: Methodsmentioning
confidence: 99%
“…Hart et al [4] analyzed the U g -value calculated from real deflections of double and triple-glazed units, measured in summer and winter at several locations in the USA. It was found that a 20 • C temperature difference reduces thermal performance by 4.6% for double-glazed IGUs and by 3.6% for triple-glazed IGUs.…”
Section: (C) (B) (A)mentioning
confidence: 99%
“…Due to the fact that heat losses through the TSEWE are directly proportional to its area, equation (8) can be used to calculate the TSEWE of different size. Since the dependence of heat loss through the TSEWE on orientation is characterized only by the coefficient of additional heat energy losses, the total losses will differ from them by the same value [33].…”
Section:  mentioning
confidence: 99%
“…[6], Arasteh D.K. [7][8][9], Hart R. [8], Goudey H. [8,9], Muhaisen A.S. [10], Klevets K. [11], Kolesnyk Y.A. [12], Zekraoui D. [13], Bülow-Hübe H. [14], Melendo J.M.A.…”
Section: Introductionmentioning
confidence: 99%